2021
DOI: 10.1371/journal.pone.0256049
|View full text |Cite
|
Sign up to set email alerts
|

High-gain observer-based nonlinear control scheme for biomechanical sit to stand movement in the presence of sensory feedback delays

Abstract: Sit-to-stand movement (STS) is a mundane activity, controlled by the central-nervous-system (CNS) via a complex neurophysiological mechanism that involves coordination of limbs for successful execution. Detailed analysis and accurate simulations of STS task have significant importance in clinical intervention, rehabilitation process, and better design for assistive devices. The CNS controls STS motion by taking inputs from proprioceptors. These input signals suffer delay in transmission to CNS making movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In addition to this, a Lyapunov-based controller was used in a linkage-based dynamic model of STS motion extracted using Lagrange's equation in the presence of sinusoidal bounded disturbances to track the desired trajectory acquired from experimental kinematic data (Nematollahi et al 2019). In two separate studies, a nonlinear control technique grounded in feedback linearization was employed to replicate the control actions of the central nervous system during the execution of STS movements (Sultan et al 2018, Sultan et al 2021.…”
Section: Modelling For Rehabilitationmentioning
confidence: 99%
“…In addition to this, a Lyapunov-based controller was used in a linkage-based dynamic model of STS motion extracted using Lagrange's equation in the presence of sinusoidal bounded disturbances to track the desired trajectory acquired from experimental kinematic data (Nematollahi et al 2019). In two separate studies, a nonlinear control technique grounded in feedback linearization was employed to replicate the control actions of the central nervous system during the execution of STS movements (Sultan et al 2018, Sultan et al 2021.…”
Section: Modelling For Rehabilitationmentioning
confidence: 99%
“…In addition, the use of control structures such as PID does not reflect optimal neural control strategies and physiological task goals for regulating seated stability. Recently, nonlinear control theory has been used to characterize the biomechanics of postural control in the sagittal plane [35,36]. Sultan et al [35] utilized a high-gain observer along with feedback linearization to simulate the behavior of the CNS for regulating standing stability in the presence of large perturbations and neural delays.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the nonlinear control paradigm, along with physiological latencies, is important for understanding the behavior of the motor control process. Sultan et al [36] also investigated the use of a high-gain observer-based feedback linearization paradigm to simulate the CNS for regulating sit-to-stand transfer. They demonstrated that such control paradigm provides an accurate simulation of the underlying dynamic system and is reliable and effective for customizing human models.…”
Section: Introductionmentioning
confidence: 99%